1996
DOI: 10.1111/j.1600-0773.1996.tb00265.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylactic Effects of U75412E Pretreatment in a Smoke‐Induced Lung Injury Rabbit Model

Abstract: The effects of the lazaroid analogue U75412E (21-[4-(3-ethylamino-2-pyridinyl)-1-piperazinyl]-16 alpha-methylpregna-1,4,9]-(11)-triene-3,20-dione) were examined in an acute lung injury rabbit model. Standard doses of 0, 8 and 16 mM U75412E were aerosolized and ventilated into the lungs for 3 min. via an endotracheal tube. A 60 tidal volume dose of diesel fuel-polycarbonate plastic smoke was then instilled, followed by mechanical ventilation for one hour. Pretreatment with 16 mM U75412E significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
3
6
1
Order By: Relevance
“…This finding is consistent with results of previous work that utilized the pretreatment of smoke-exposed animals with U75412E (34,35). Lazaroid treatment prevented smoke-induced changes in blood Pa02, PaC02, pH, and COHb°lo.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with results of previous work that utilized the pretreatment of smoke-exposed animals with U75412E (34,35). Lazaroid treatment prevented smoke-induced changes in blood Pa02, PaC02, pH, and COHb°lo.…”
Section: Discussionsupporting
confidence: 92%
“…Administration of aerosolized lazaroid, U75412E, significantly attenuated smoke-induced changes in alveolar hypoventilation, BAL total protein and 6-keto-PGF1-a levels, and epithelial injury. U75412E appears to preserve respiratory epithelial cell structure possibly through modulating AA metabolism, in addition to its characterized antioxidative mechanisms (4,5,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in our laboratory with this model have demonstrated that smoke-induced lung injury was involved in a complex series of events in the lung includ ing the time-phase changes of PAM 03 production, PAM TNF-a release, and lung permeability [12,[26][27][28], We found that PAM 03 production cx vivo decreases 2 h and conversely, increases 24 h after cell isolation and culture in a 1-hour smoke experiment [32]. Therefore, this inves tigation was designed fora comparison between pretreat ment and posttreatment with U75412E in this model, due to a biphasic response of PAM O] production.…”
Section: Discussionmentioning
confidence: 55%
“…Our FS exposure protocol and the chemical characteristics of this particular type of smoke have been described in detail in previous studies (44,48). Briefly, 30 ml of diesel fuel were placed in a ceramic crucible and burned in a stainless steel smoke chamber.…”
Section: Fs Exposurementioning
confidence: 99%